Calidad percibida y satisfacción de los espectadores de fútbol - Antonio Navarro-García; María Eugenia Reyes-García; Francisco J. Acedo-González (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2014)
– The main objective of this study is to determine the influence of service quality on satisfaction of football spectators, looking scarcely investigated in the literature. The results, from a sample of 700 spectators at a football club of the Spanish First Division, reveal three main conclusions: (i) the quality of service of a football event is determined by both tangibles - infrastructure - as intangible - quality and delivery of equipment, and management of the board; (ii) the quality of positively affects service satisfaction experienced by the viewer part associated with football event; (iii) in overall satisfaction directly influences partial satisfaction associated with specific aspects of the sporting event and indirectly the quality of services provided. The study concludes with the main contributions, limitations and future research.
Keywords: M31; 330; Perceived quality; Service; Customer satisfaction; Sport event; Football